PENGARUH PAJAK PENGHASILAN BADAN TERHADAP KINERJA KEUANGAN (Studi Kasus pada Delapan Perusahaan Sektor Kesehatan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2022) - Sholihati, Lilis; Kiswara, Endang (Diponegoro Journal of Accounting, 2024)
The aim of this research is to analyze the impact of corporate income tax on financial performance. The financial performance in this study is the company's profitability measured by return on assets (ROA), return on investment (ROI), and return on equity (ROE) in healthcare sector companies listed on the Indonesia Stock Exchange from 2017 to 2022.The data used in this research is secondary data in the form of financial statements of healthcare sector companies listed on the Indonesia Stock Exchange from 2017 to 2022. A purposive sampling technique was used to select the sample, which consisted of eight healthcare sector companies. Regarding data analysis, the non-parametric test method with Spearman correlation test and Wilcoxon Signed Rank Test were used in this study.The results of the study indicate that there is a significant difference between income tax and financial performance measured by ROA after the tax rate change due to the Covid-19 pandemic. In addition, there is no significant difference in the relationship between income tax and financial performance measured by ROI and ROE after the tax rate change.